2010
DOI: 10.1089/fpd.2010.0561
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation ofCampylobacter jejuniby Exposure to High-Intensity 405-nm Visible Light

Abstract: Although considerable research has been carried out on a range of environmental factors that impact on the survival of Campylobacter jejuni, there is limited information on the effects of violet/blue light on this pathogen. This investigation was carried out to determine the effects of high-intensity 405-nm light on C. jejuni and to compare this with the effects on two other important Gram-negative enteric pathogens, Salmonella enteritidis and Escherichia coli O157:H7. High-intensity 405-nm light generated fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
35
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(46 citation statements)
references
References 35 publications
(45 reference statements)
9
35
2
Order By: Relevance
“…sonnei to 405 nm light also demonstrated significant bacterial inactivation, with the inactivation kinetics of all the organisms investigated in this study showing a similar sigmoidal shape to those from previous studies on the bactericidal effect of 405 nm light (12,13,18). Treatment of L. monocytogenes and the other Listeria species using the 405 nm LED array resulted in similar inactivation kinetics, suggesting that bacteria within the same genus may undergo very similar inactivation reactions.…”
Section: Discussionsupporting
confidence: 82%
“…sonnei to 405 nm light also demonstrated significant bacterial inactivation, with the inactivation kinetics of all the organisms investigated in this study showing a similar sigmoidal shape to those from previous studies on the bactericidal effect of 405 nm light (12,13,18). Treatment of L. monocytogenes and the other Listeria species using the 405 nm LED array resulted in similar inactivation kinetics, suggesting that bacteria within the same genus may undergo very similar inactivation reactions.…”
Section: Discussionsupporting
confidence: 82%
“…These differences in the effectiveness of 405 nm LED illumination might be due to the different experimental design such as the distance between LED and bacterial suspension, total volume and depth of bacterial suspension, initial population and set temperature Murdoch et al, 2010). In particular, the previous studies used magnetic stirring plate to agitate bacterial suspension during the illumination, probably maximizing its antibacterial effect Murdoch et al, 2010). However, the bacterial suspension was not agitated during illumination in the present study to simulate a food matrix.…”
Section: Discussionmentioning
confidence: 94%
“…Another study carried by Murdoch, Maclean, Endarko, MacGregor, and Anderson (2012) with 405 nm LED at the irradiance of 10 mW/cm 2 demonstrated that 5-log reductions of S. sonnei and E. coli O157:H7 were achieved at 180 and 288 J/cm 2 (5 and 8 h), respectively. These differences in the effectiveness of 405 nm LED illumination might be due to the different experimental design such as the distance between LED and bacterial suspension, total volume and depth of bacterial suspension, initial population and set temperature Murdoch et al, 2010). In particular, the previous studies used magnetic stirring plate to agitate bacterial suspension during the illumination, probably maximizing its antibacterial effect Murdoch et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations